Additive manufacturing aluminum-silicon alloy and preparation method of powder and test piece of additive manufacturing aluminum-silicon alloy
By adding Nb and B in the additively manufactured aluminum-silicon alloy, and activate heteronucleation using the supercooling degree generated at the front edge of the solid/liquid interface, the problem of poor plasticity and plastic anisotropy of the aluminum-silicon alloy is solved, and a significant improvement in mechanical properties is achieved.
Patent Information
- Application Number
- CN202510127874.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-18
AI Technical Summary
Existing additively manufactured aluminum-silicon alloys have poor performance in plasticity and plastic anisotropy, resulting in structural parts prone to failure under extreme stresses and affecting their fatigue life and service life.
By adding the solute elements Nb and B of high growth restriction factors in the aluminum-silicon alloy, the supercooling degree ΔTCS of the component rapidly generated at the front edge of the solid/liquid interface is activated, the epitaxial growth of columnar crystals is broken, and the grain orientation distribution is improved.
It significantly improves the plasticity of aluminum-silicon alloy and reduces plastic anisotropy, and improves the mechanical properties of the material, including yield strength, tensile strength and after-break elongation.
Smart Images

Figure CN119843115A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal additive manufacturing, and specifically relates to a method for preparing an additively manufactured aluminum-silicon alloy and powder and a test piece thereof. Background Art
[0002] At present, aluminum alloy structural parts are mainly manufactured by traditional methods such as casting, forging, extrusion and powder metallurgy. Although aluminum alloy products produced by the above traditional processes have been widely used, there are still many problems in the production process and application. First, the low cooling rate in the casting process makes the structure coarse, and there are many defects in the cast aluminum alloy, such as shrinkage, slag inclusions, element segregation, etc., which reduce the mechanical properties of the parts. Secondly, the preparation and forming processes of high-performance aluminum alloy components are separated, resulting in long processing cycles and low flexibility. In addition, with the development of modern industry, the structural and performance requirements of aluminum alloy parts are constantly increasing. The production of aluminum alloy parts with diverse structures, high dimensional accuracy and near-net shape will be the main research and development goal in the future.
[0003] At present, laser additive manufacturing (SLM) technology has been widely used in aluminum alloys. Due to the ultra-fast cooling rate of SLM, the microstructure of the deposited aluminum-silicon alloy sample is usually an ultra-fine cellular structure with a diameter of about 500 nanometers. This microstructural feature will lead to back stress strain hardening during plastic deformation, thereby improving the strain hardening ability of the material. Therefore, SLM-formed aluminum-silicon alloys usually have excellent tensile properties, with a yield strength of more than 250 MPa and a tensile strength of more than 400 MPa. However, the high strain hardening ability does not give SLM-formed aluminum-silicon alloys excellent plasticity, and its elongation in the horizontal direction is only about 7%. Worse, the elongation in the vertical direction is only about 4%, and there is severe plastic anisotropy. This lack of plasticity and severe plastic anisotropy will not only cause catastrophic failure of structural parts under unexpected extreme stress, but also reduce fatigue life, thereby affecting the service life and reliability of the parts. On the other hand, although additive manufacturing parts can achieve near-net shape, they may still require subsequent processing and assembly, and plasticity is an important indicator affecting machinability. At present, aluminum-silicon alloy specimens are often used as aerospace or automotive parts. The rapid and strong connection of these parts will inevitably use the self-piercing riveting (SPR) process, which usually requires the alloy to have a ductility of more than 10% to ensure that the parts will not crack when the rivet pierces, thereby forming a strong mechanical bond. However, the plasticity of the current additively manufactured aluminum-silicon alloy basically does not meet the above indicators, so there is an urgent need to develop an additively manufactured aluminum-silicon alloy with high plasticity and isotropic plasticity. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an additively manufactured aluminum-silicon alloy in view of the above-mentioned deficiencies of the prior art. The aluminum-silicon alloy is based on the existing commercial alloy grades, and a sufficient Δ T CS , further affecting the Δ T , to provide additional driving force to activate heterogeneous nucleation. T It is not enough to completely transform the columnar crystals in the solidification structure into equiaxed crystals, but the Δ T CS The addition of some heterogeneous nucleation particles helps to break the epitaxial growth of columnar crystals, eliminate the coarse columnar crystals growing across the molten pool, reduce the texture strength, and obtain grains with more uniform orientation distribution, thereby improving the plasticity and plastic anisotropy of additively manufactured aluminum-silicon alloys, which is of great significance for broadening its application range.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a Nb-containing plastic isotropic additively manufactured aluminum-silicon alloy, characterized in that it is composed of the following elements in mass percentage: Si: 9.5-10.5%, Mg: 0-0.5%, Nb: 0.05-0.15%, B: 0.005-0.05%, and the remainder is Al and unavoidable impurity elements; the mass percentage of Nb and B does not exceed 0.2%.
[0006] In the additively manufactured aluminum-silicon alloy of the present invention, the Si element is beneficial to improving the fluidity of the solution, increasing the solidification range, reducing the tendency of solidification cracking, and is beneficial to improving the additive manufacturing processability of the alloy; the Mg element plays a role in solid solution strengthening and aging strengthening, which is beneficial to improving the strength of the alloy; the Nb and B elements have high growth restriction factors, and the B element promotes the inoculation effect of the Nb element. In addition to quickly generating sufficient component supercooling Δ at the front of the growing solid / liquid interface T CS , further affecting the supercooling Δ at the solid / liquid interface front T , and can also form effective nucleation particles (NbB2 and Al3Nb), providing additional driving force to activate heterogeneous nucleation, thereby improving the grain structure of additively manufactured aluminum-silicon alloys, making the grain orientation distribution more uniform, and achieving a significant improvement in plasticity and plastic isotropy.
[0007] Preferably, the Nb and B are solute elements with high growth limiting factors. In the additively manufactured aluminum-silicon alloy, at least 50% of the mass percentage of Nb and B are respectively dissolved in the aluminum matrix. The AlNbB master alloy is used as a carrier to produce component supercooling, and the remaining Nb and B elements exist in the form of NbB2 and Al3Nb particles, and the Al3Nb particle size is less than 2μm, and the NbB2 particle size is less than 100nm.
[0008] Preferably, the following components are included by mass percentage: Si: 9.5-10.5%, Mg: 0.35-0.5%, Nb: 0.06-0.1%, B: 0.005-0.01%, the remainder is Al and unavoidable impurity elements, and the mass percentage of Nb and B does not exceed 0.11%.
[0009] Preferably, the mass ratio of Nb to B is (1-15):1, Preferably, the mass ratio of Nb to B is 10:1.
[0010] The present invention also provides a method for preparing powder of aluminum-silicon alloy containing Nb for plastic isotropic additive manufacturing, which comprises: taking high-purity Al, Al-Si master alloy, high-purity Mg and AlNbB master alloy according to the designed composition, putting them into a vacuum induction furnace, first evacuating the furnace, and setting the pressure in the furnace to ≤10 -1 Pa, then heat up and introduce protective gas; heat to 800-900℃, keep warm for at least 15-30 min to mix the alloy elements evenly, transfer the completely melted and evenly mixed alloy liquid into an atomizing powder spraying crucible, introduce inert gas for atomization and powder making, the atomization pressure is 0.5-10 MPa, the nozzle diameter used for atomization is 0.5-5 mm, and aluminum silicon alloy powder is obtained.
[0011] The method for preparing aluminum-silicon alloy powder of the present invention does not require the pre-preparation of a master alloy ingot, and the stability of the components in the obtained alloy powder can be ensured. This is because trace amounts of Nb and B are added to the aluminum-silicon alloy of the present invention, and the addition of trace amounts of Nb and B will not affect the fluidity of the alloy melt, and therefore will not affect the atomization process parameters of the original alloy.
[0012] The present invention also provides a test piece, which is prepared by using the aluminum-silicon alloy powder prepared according to claim 6 and utilizing a selective laser melting method.
[0013] Preferably, the test piece is prepared by a selective laser melting method, which specifically includes the following steps: S1. Draw the three-dimensional graphics of the required parts through software; S2, screening and selecting aluminum-silicon alloy powder with a particle size range of 15-53 μm, and drying the aluminum-silicon alloy powder in a vacuum drying oven; using the dried aluminum-silicon alloy powder to prepare a deposited sample according to the three-dimensional graph drawn in step S1 by a selective laser melting method; the plastic anisotropy of the deposited sample does not exceed 15%; S3. Heat-treating the sample obtained in step S2 to obtain a specimen having mechanical properties that meet the requirements of a specific application scenario; the plastic anisotropy of the specimen does not exceed 20%.
[0014] Preferably, the process parameters for drying the aluminum-silicon alloy powder in S2 are: temperature 80-150°C, insulation 2-6 h; the process parameters for the selective laser melting method are: laser power 220-340W, scanning speed 1200-1700mm / s, spot size 60-100 μm, scanning interval 0.13-0.17mm, layer thickness 30-60 μm; the obtained deposited sample does not have coarse columnar crystals growing across the molten pool, the grain orientation is evenly distributed and there is no obvious texture.
[0015] Preferably, the process parameters of the heat treatment in S3 are: heating temperature 165-300° C., holding time 2-4 h, followed by air cooling.
[0016] Compared with the prior art, the present invention has the following advantages: The present invention consulted a large amount of data and designed multiple experiments for verification in the early stage of research, and found that the shortcomings of SLM-formed aluminum-silicon alloys are attributed to the lower density of the sample, rough columnar grains, texture or uneven microstructure between adjacent molten pools. During the SLM process, nucleation usually occurs at the bottom of the molten pool, and then the grains grow along the direction of the thermal gradient. However, in order to eliminate the energy required for nucleation, the grains usually tend to rely on epitaxial growth in the directional solidification mode of the upper layer. Therefore, SLM-formed aluminum-silicon alloys usually exhibit a grain structure with a higher texture, and a large number of columnar grains span multiple molten pools. This microstructural feature usually leads to plastic deterioration and severe plastic anisotropy.
[0017] According to the nucleation theory of Winegard and Chalmers and the interdependence theory, the basic condition for activating heterogeneous nucleation and thus inhibiting columnar or epitaxial growth is to produce sufficient undercooling (Δ T ), to exceed the critical undercooling required for heterogeneous nucleation (Δ T n ), that is, Δ T ≥Δ T n . Δ T is thermal supercooling (Δ Tt ) and compositional supercooling (Δ T CS ), Δ T t is caused by the hysteresis effect of the actual growth rate of the solid / liquid interface compared with the theoretical growth rate caused by the cooling rate of the melt, Δ T CS The formation of the solid / liquid interface is closely related to the solute distribution in front of the solid / liquid interface. In the additive manufacturing process, the rapid solidification of the tiny molten pool is accompanied by a large thermal gradient, usually within 10 5 Up to 10 7 Despite the presence of growth-limiting solutes, such a steep thermal gradient will significantly limit the compositional supercooling region at the solid / liquid interface front, thus limiting Δ T CS In addition to the sharp thermal gradient, melt pool solidification is also associated with a high cooling rate, which leads to a large thermal undercooling Δ T t Therefore, in the absence of effective nucleation particles, the critical nucleation condition (i.e., Δ T ≥Δ T n ) becomes challenging, and this confined undercooling region leads to columnar grain growth. T n It is closely related to the interface energy between the nucleation particles and the matrix metal. The smaller the lattice mismatch between the nucleation particles and the matrix crystal, the T n The lower.
[0018] A large number of current studies focus on promoting heterogeneous nucleation in the supercooling zone by introducing nucleating agents with good lattice matching with the base metal into the melt, limiting grain growth, and ultimately leading to grain refinement and columnar to equiaxed transformation (CET), i.e., inoculation treatment. Effective nucleating particles in additive manufacturing include Al3X, such as Zr, Sc, Ti, and compounds such as TiB2 and LaB6. Due to the limited supercooling zone at the front of the solid / liquid interface caused by the unique melting and solidification mode of the additive manufacturing process, the complete CET in additive manufacturing requires heterogeneous nucleating particles with higher content and smaller size. The uniform distribution of these nanoparticles in the molten pool also depends largely on the proper preparation of powder raw materials, involving powder modification (including mechanical ball milling, electrostatic assembly) and pre-alloying technology. However, the powder modification method will reduce the powder fluidity and may damage the mechanical properties of the final product; in contrast, the pre-alloying method is to prepare an alloy ingot with a target composition by traditional casting, and then produce powder by atomization process, so it is more complex and costly. In addition, although inoculation treatment is widely used in the additive manufacturing of aluminum alloys, in order to achieve significant grain refinement, a large amount of nanoparticles is usually required, which leads to a significant deviation between the chemical composition of the alloy and the standard composition, resulting in new alloys. Standardization and classification of new alloys and certification of their applications are crucial, especially in the aerospace industry, which makes it difficult to promote new alloys designed by inoculation treatment methods.
[0019] Based on the theoretical research conclusions of the present invention, the additively manufactured aluminum-silicon alloy of the present invention rapidly generates sufficient Δ T CS , further affecting the Δ T , to provide additional driving force to activate heterogeneous nucleation; the simultaneous formation of NbB2 and Al3Nb particles reduces Δ T n , promoting heterogeneous nucleation. This is different from the prior art that a large amount of nano-nucleation particles are added (reducing Δ T n , including Al3X, such as Zr, Sc, Ti, and compounds such as TiB2 and LaB6) and growth-limiting solutes (increasing Δ T CS , Ti, Zr, V, Si, Nb and other solute elements) to achieve complete CET of grains and improve performance anisotropy. The present invention only needs to add a trace amount of high growth-limiting solute, which reduces the critical nucleation undercooling Δ T n , and provide sufficient Δ T CS To generate an additional Δ T, promoting heterogeneous nucleation. The additively manufactured aluminum-silicon alloy of the present invention does not achieve complete CET of the grains, but obtains a more uniform grain orientation distribution through the inoculation of Nb and B. Therefore, even if there are still columnar crystals inside the molten pool, the small-angle grain boundaries within the columnar crystals will reduce their texture, which is conducive to better mechanical properties.
[0020] At the same time, compared with the powder modification (including mechanical ball milling, electrostatic assembly) and pre-alloying technology of the prior art, the method for preparing the Nb-containing plastic isotropic additive manufacturing aluminum-silicon alloy powder of the present invention only needs to add AlNbB master alloy in the batching link of the atomization powder making process, and the alloy elements are evenly mixed to achieve uniform distribution of Nb and B. There is no need to pre-prepare alloy ingots with target components or perform complicated modification treatment on the powder. Therefore, the process flow of the additive manufacturing aluminum-silicon alloy powder preparation method of the present invention is simpler and the cost is lower.
[0021] The Nb-containing plastic isotropic additively manufactured aluminum-silicon alloy powder of the present invention is improved by microalloying the existing commercial aluminum-silicon alloy without changing its standard chemical composition range. Therefore, the Nb-containing plastic isotropic additively manufactured aluminum-silicon alloy powder of the present invention can directly replace the application scenarios of existing commercial aluminum-silicon alloys without the need for new material certification.
[0022] The test piece obtained by the present invention has excellent SLM formability and a density of more than 99.8%, which solves the problem of low plasticity and severe plastic anisotropy of SLM-formed aluminum-silicon alloys and broadens its application in the aerospace industry. The yield strength of the deposited sample is up to 300 MPa, the tensile strength is 500 MPa, the elongation after fracture is 12%, and the plastic anisotropy is reduced to 8%.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Solidification path of aluminum-silicon alloy in Example 1 obtained based on thermodynamic calculation; Figure 2 SEM photo of the original aluminum-silicon alloy powder in Example 1 of the present invention; Figure 3 SEM photo of the microstructure of the deposited sample obtained in Example 1 of the present invention; Figure 4 The grain orientation distribution diagram of the deposited sample obtained in Example 1 of the present invention; Figure 5 The grain Schmidt factor distribution diagram of the deposited sample obtained in Example 1 of the present invention; Figure 6The mechanical properties of the AlSi10Mg alloy containing Nb additively manufactured in Example 1 of the present invention are compared with the properties of the currently reported AlSi10Mg alloy; Figure 7 Grain orientation distribution diagram of the AlSi10Mg alloy sample manufactured by additive manufacturing in Comparative Example 1 of the present invention; Figure 8 The grain Schmidt factor distribution diagram of the deposited sample obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clear, the following is a further detailed description of the modification of AlSi10Mg alloy by adding trace amounts of Nb and B. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example
[0026] The present embodiment discloses an aluminum-silicon alloy for additive manufacturing, and its alloy composition is shown in Table 1. Figure 1 The solidification path of the additively manufactured aluminum-silicon alloy containing Nb in Example 1 is obtained based on thermodynamic calculations, reflecting the change in phase volume fraction during the additive manufacturing process.
[0027] Table 1 Chemical composition of elements of aluminum-silicon alloy in Example 1 (mass percentage) Si Mg Nb B Al 9.5 0.35 0.1 0.01 Bal. The method for preparing the powder of the aluminum-silicon alloy containing Nb for plastic isotropic additive manufacturing in this embodiment specifically comprises the following steps: S1. Considering the burning loss of alloy elements, the materials are prepared according to the designed composition. High-purity Al, Al-Si master alloy, high-purity Mg and AlNbB master alloy are placed in a vacuum induction furnace, and then vacuumed to a furnace pressure of ≤10 -1 Pa; SEM observations revealed the presence of micron-sized Al3Nb particles and nano-sized NbB2 particles in the AlNbB master alloy; S2, turn on the power to heat up and introduce high-purity argon gas to make the gas pressure in the smelting furnace slightly lower than the atmospheric pressure to prevent argon gas leakage; S3, heating to 850°C, keeping the temperature for 30 minutes, and using the electromagnetic stirring effect of the vacuum induction furnace to mix the alloy elements evenly; S4. The completely melted and evenly mixed alloy liquid is transferred into an atomized powder spraying crucible, and argon gas is introduced for atomization powder making (atomization pressure is 2 MPa, and the nozzle diameter used for atomization is 1.5 mm) to obtain aluminum-silicon alloy powder. At this time, the aluminum-silicon alloy powder particle size range is 0-180 μm. The aluminum-silicon alloy powder with a particle size of 15-53 μm is selected as the aluminum-silicon alloy powder for additive manufacturing. The powder morphology is as follows: Figure 2 shown.
[0028] The test piece is prepared by using the above-mentioned additive manufacturing aluminum-silicon alloy powder, including the following steps: S1. Draw the three-dimensional graphics of the required specimen through software; S2. Dry the selected additive manufacturing aluminum silicon alloy powder in a vacuum drying oven at 100°C for 4 hours; use the dried powder to prepare the required deposited sample using a BLT S210 printer; the process parameters of the selective laser melting method are: spot size 60 μm, process parameters are laser power 230 W, scanning speed 1700 mm / s, scanning spacing 170 μm, and layer thickness 30 μm; S3. The deposited sample was polished, the porosity was counted by optical microscopy, and the density of the sample was measured by Archimedes drainage method to be 99.8%. The microstructure of the deposited sample was characterized by scanning electron microscopy (SEM). Figure 3 As shown; EBSD and TEM characterization of the deposited samples revealed that the alloy still had a large number of cellular structures, and the size of the cellular structures was about 500 nm. HADDF images and EDS confirmed that there were still a small number of Al3Nb particles with a size less than 2 μm and NbB2 particles with a size less than 100 nm in the structure, and 0.05 wt.% Nb element and 0.005 wt.% B element were dissolved in the matrix. EBSD characterization of the deposited sample, grain structure and texture Figure 4 As shown. Although obvious columnar crystal structure can still be observed, the coarse columnar crystals growing across the molten pool have been eliminated, and the texture strength has been significantly reduced (the MUD values of the sample cross section and longitudinal section are 1.36 and 1.56, respectively); according to statistics, the average grain size of the sample cross section and longitudinal section is 4.5μm and 6.7μm, respectively. The grain Schmidt factor distribution diagram obtained by EBSD data analysis shows that the proportion of grains with high Schmidt factor is reduced, and the grain orientation distribution is more uniform, as shown in Figure 5 As shown; S4. In some application scenarios, the specimen is required to have a higher yield strength, and the requirements for plasticity and plastic anisotropy are lower. In order to meet the mechanical performance indicators required by specific application scenarios, the deposited sample is heat treated, heated to 165°C for 4 h, and then air-cooled to obtain the specimen.
[0029] In order to verify the effect of Example 1, relevant tests were carried out on the yield strength, tensile strength and elongation of the deposited samples and specimens. The yield strength of the transverse deposited sample was 300 MPa, the tensile strength was 480 MPa, and the elongation was 12%; the yield strength of the longitudinal deposited sample was 260 MPa, the tensile strength was 498 MPa, and the elongation was 11%; the plastic anisotropy was 8.3%. The yield strength of the transverse specimen after heat treatment was 350 MPa, the tensile strength was 486 MPa, and the elongation was 6.5%; the yield strength of the longitudinal specimen after heat treatment was 320 MPa, the tensile strength was 505 MPa, and the elongation was 5.9%; the plastic anisotropy was 9.2%. The mechanical properties of the aluminum-silicon alloy manufactured by additive manufacturing containing Nb in this example are compared with the properties of the currently reported AlSi10Mg alloy. Figure 6 As shown. Figure 6 As shown by the large dashed circle in (a), the tensile properties of pure AlSi10Mg manufactured by additive manufacturing in the prior art vary greatly, which is due to differences in processing parameters, powder quality, platform preheating temperature, scanning strategy, etc. In contrast, compared with pure AlSi10Mg manufactured by additive manufacturing in the prior art, the AlSi10Mg manufactured by additive manufacturing containing Nb in the present invention has excellent strength and unprecedented plasticity. In addition, as Figure 6 As shown by the dotted circle in (b), the additively manufactured AlSi10Mg not only has serious deficiencies in plasticity, but also has serious plastic anisotropy. In contrast, the Nb-containing additively manufactured AlSi10Mg of the present invention shows obvious advantages in both aspects. Example
[0030] The aluminum-silicon alloy powder prepared in Example 1 was used to prepare the sample using a BLT A320 printer. The process parameters of the selective laser melting method were: spot size 100 μm, laser power 240 W, scanning speed 1300 mm / s, scanning spacing 170 μm, layer thickness 30 μm, and other conditions were the same as in Example 1.
[0031] The density of the deposited sample was measured by the Archimedes drainage method to be 99.6%. The mechanical properties of the deposited samples were characterized. The yield strength of the transverse sample was 287 MPa, the tensile strength was 447 MPa, and the elongation after fracture was 7.8%; the yield strength of the longitudinal sample was 290 MPa, the tensile strength was 450 MPa, and the elongation after fracture was 7.2%; the plastic anisotropy was 8%. Example
[0032] The aluminum-silicon alloy powder prepared in Example 1 was used to prepare the sample using a BLT A320 printer. The process parameters of the selective laser melting method were: spot size 100 μm, laser power 340 W, scanning speed 1400 mm / s, scanning spacing 130 μm, layer thickness 50 μm, and other conditions were the same as in Example 1.
[0033] The density of the deposited sample was measured by the Archimedes drainage method to be 99.8%. The mechanical properties of the deposited samples were characterized. The yield strength of the transverse sample was 277 MPa, the tensile strength was 460 MPa, and the elongation after fracture was 10.9%; the yield strength of the longitudinal sample was 257 MPa, the tensile strength was 458 MPa, and the elongation after fracture was 9.8%; the plastic anisotropy was 10%. Example
[0034] The aluminum-silicon alloy powder prepared in Example 1 was used to prepare the sample using a BLT A320 printer. The process parameters of the selective laser melting method were: spot size 100 μm, laser power 230 W, scanning speed 1700 mm / s, scanning spacing 130 μm, layer thickness 60 μm, and other conditions were the same as in Example 1.
[0035] The density of the deposited sample was measured by the Archimedes drainage method to be 99.7%. The mechanical properties of the deposited samples were characterized. The yield strength of the transverse sample was 278 MPa, the tensile strength was 458 MPa, and the elongation after fracture was 9.2%; the yield strength of the longitudinal sample was 251 MPa, the tensile strength was 448 MPa, and the elongation after fracture was 8.1%; the plastic anisotropy was 12%. Example
[0036] The aluminum-silicon alloy powder prepared in Example 1 was used to prepare a sample using the printing equipment and printing parameters in Example 3; the heat treatment temperature was 200° C. and the heat preservation was 2 h; other conditions were the same as in Example 1.
[0037] After heat treatment, the as-deposited yield strength of the transverse specimen is 275 MPa, the tensile strength is 396 MPa, and the elongation after fracture is 7%; the as-deposited yield strength of the longitudinal specimen is 257 MPa, the tensile strength is 372 MPa, and the elongation after fracture is 5.7%; the plastic anisotropy is 18%. Example
[0038] The aluminum-silicon alloy powder prepared in Example 1 was used to prepare a sample using the printing equipment and printing parameters in Example 3; the heat treatment temperature was 300° C. and the temperature was kept for 3 h; other conditions were the same as in Example 1.
[0039] After heat treatment, the as-deposited yield strength of the transverse specimen is 201 MPa, the tensile strength is 306 MPa, and the elongation after fracture is 13.5%; the as-deposited yield strength of the longitudinal specimen is 182 MPa, the tensile strength is 283 MPa, and the elongation after fracture is 12.8%; the plastic anisotropy is 5%. Example
[0040] The alloy composition in this embodiment is shown in Table 2. The performance test sample is prepared from the Nb-containing aluminum-silicon alloy powder using a BLT S210 printer. The spot size is 60 μm, the process parameters are laser power 220 W, scanning speed 1400 mm / s, scanning spacing 150 μm, and layer thickness 30 μm; the heat treatment temperature is 170 ° C and the heat preservation is 2 h; other conditions are the same as in Example 1.
[0041] Table 2 Chemical composition of the initial aluminum-silicon alloy powder in Example 5 (mass percentage) Si Mg Nb B Al 10.5 0.5 0.06 0.005 Bal. The density of the deposited sample was measured by the Archimedes drainage method to be 99.8%. The mechanical properties of the deposited samples were characterized. The yield strength of the transverse sample was 282 MPa, the tensile strength was 465 MPa, and the elongation after fracture was 11%; the yield strength of the longitudinal sample was 230 MPa, the tensile strength was 486 MPa, and the elongation after fracture was 9.5%; the plastic anisotropy was 13.6%. After heat treatment, the yield strength of the transverse sample was 315 MPa, the tensile strength was 466 MPa, and the elongation after fracture was 9%; the yield strength of the longitudinal sample was 284 MPa, the tensile strength was 500 MPa, and the elongation after fracture was 7.5%; the plastic anisotropy was 17%.
[0042] The aluminum silicon alloy in this comparative example is a commercial AlSi10Mg alloy, without adding the modifying elements Nb and B. The method for preparing the commercial AlSi0Mg alloy powder and the method for preparing the test piece using the commercial AlSi0Mg alloy powder are the same as those in Example 1.
[0043] The density of the deposited sample was measured by the Archimedes drainage method to be 99.7%. The grain structure and texture of the deposited sample of the additively manufactured AlSi0Mg alloy in this comparative example are as follows: Figure 7 As shown, coarse columnar grains growing across multiple layers of molten pools can be observed; the MUD values of the cross section and longitudinal section of the deposited sample prepared in this comparative example are 2.67 and 3.25, respectively, indicating the presence of a relatively obvious texture; according to statistics, the average grain sizes of the cross section and longitudinal section of the deposited sample prepared in this comparative example are 5.7 μm and 7.4 μm, respectively. The grain Schmidt factor distribution diagram obtained by EBSD data analysis shows that grains with high Schmidt factors account for a large proportion, and the grains have obvious preferred orientation, such as Figure 8 shown.
[0044] The mechanical properties of the deposited samples and specimens prepared in this comparative example were characterized. The yield strength of the deposited transverse sample was 274 MPa, the tensile strength was 445 MPa, and the elongation after fracture was 7.6%; the yield strength of the deposited longitudinal sample was 250 MPa, the tensile strength was 425 MPa, and the elongation after fracture was 4.5%; the plastic anisotropy was 40.8%. After heat treatment, the yield strength of the transverse specimen was 311 MPa, the tensile strength was 454 MPa, and the elongation after fracture was 5%; the yield strength of the longitudinal specimen was 290 MPa, the tensile strength was 430 MPa, and the elongation after fracture was 3.5%; the plastic anisotropy was 30%. Therefore, the mechanical properties of the deposited samples and specimens prepared in this comparative example were not as good as those of Example 1, showing obvious plastic anisotropy.
[0045] In this embodiment, the alloy composition is shown in Table 3, and the effect of excessive addition of Nb and B on the plastic anisotropy of the additively manufactured aluminum-silicon alloy is studied. The performance test specimens were prepared from the aluminum-silicon alloy powder containing Nb using a BLT A320 printer, with a spot size of 100 μm, process parameters of laser power of 230 W, scanning speed of 1200 mm / s, scanning spacing of 170 μm, and layer thickness of 30 μm; other conditions were the same as in Example 1.
[0046] Table 3 Chemical composition of the initial aluminum-silicon alloy powder in Example 5 (mass percentage) Si Mg Nb B Al 9.8 0.38 0.2 0.08 Bal. The density of the deposited sample was measured by the Archimedes drainage method to be 99.1%. The mechanical properties of the deposited samples were characterized. The yield strength of the transverse sample was 293 MPa, the tensile strength was 491 MPa, and the elongation after fracture was 7%; the yield strength of the longitudinal sample was 283 MPa, the tensile strength was 444 MPa, and the elongation after fracture was 4.4%; the plastic anisotropy was 37%.
[0047] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An additively manufactured aluminum-silicon alloy, characterized in that: The following elements are present in percentage by mass Composition: Si: 9.5-10.5%, Mg: 0-0.5%, Nb: 0.05-0.15%, B: 0.005-0.05%, the balance is Al and unavoidable impurity elements; the mass percentage of Nb and B does not exceed 0.2%.
2. The aluminum-silicon alloy powder for additive manufacturing according to claim 1, characterized in that: The Nb and B are solute elements with high growth limiting factors. In the additively manufactured aluminum-silicon alloy, at least 50% of the mass percentage of Nb and B are respectively dissolved in the aluminum matrix. The AlNbB master alloy is used as a carrier to produce component supercooling. The remaining Nb and B elements exist in the form of NbB2 and Al3Nb particles, and the Al3Nb particle size is less than 2μm, and the NbB2 particle size is less than 100nm.
3. The additive manufacturing aluminum-silicon alloy powder according to claim 1, characterized in that: The following components are included in mass percentage: Si: 9.5-10.5%, Mg: 0.35-0.5%, Nb: 0.06-0.1%, B: 0.005-0.01%, the remainder is Al and unavoidable impurity elements, and the mass percentage of Nb and B does not exceed 0.11%.
4. The aluminum-silicon alloy powder for additive manufacturing according to claim 1 or 2, characterized in that: The mass ratio of Nb to B is (1-15):
1.
5. The aluminum-silicon alloy powder for additive manufacturing according to claim 4, characterized in that: The mass ratio of Nb to B is 10:
1.
6. A method for preparing powder for additive manufacturing of aluminum-silicon alloy according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: taking raw materials according to the designed composition, putting them into a vacuum induction furnace, first evacuating the vacuum, then heating and introducing a protective gas; heating the furnace to 800-900°C, keeping the temperature for at least 15-30 minutes to evenly mix the alloy elements, transferring the completely melted and evenly mixed alloy liquid into an atomizing powder spraying crucible, introducing an inert gas for atomization and powdering, and obtaining aluminum silicon alloy powder; the raw materials are high-purity Al, Al-Si master alloy, high-purity Mg and AlNbB master alloy.
7. A method for preparing an aluminum-silicon alloy specimen by additive manufacturing, characterized in that: The aluminum-silicon alloy powder prepared according to claim 6 is used to prepare a test piece using a selective laser melting method.
8. The preparation method according to claim 7, characterized in that: The test piece is prepared by using the selective laser melting method, which specifically includes the following steps: S1. Draw the three-dimensional graphics of the required specimen through software; S2, screening and selecting aluminum-silicon alloy powder with a particle size range of 15-53 μm, and drying the aluminum-silicon alloy powder in a vacuum drying oven; using the dried aluminum-silicon alloy powder to prepare a deposited sample according to the three-dimensional graph drawn in step S1 by a selective laser melting method; the plastic anisotropy of the deposited sample does not exceed 15%; S3. Heat-treating the sample obtained in step S2 to obtain a specimen having mechanical properties that meet the requirements of a specific application scenario; the plastic anisotropy of the specimen does not exceed 20%.
9. The preparation method according to claim 8, characterized in that: The process parameters for drying the aluminum-silicon alloy powder in S2 are: temperature 80-150℃, insulation 2-6 h; the process parameters for the selective laser melting method are: laser power 220-340W, scanning speed 1200-1700mm / s, spot size 60-100 μm, scanning interval 0.13-0.17mm, layer thickness 30-60 μm; the deposited sample obtained does not have coarse columnar crystals growing across the molten pool, the grain orientation is evenly distributed and there is no obvious texture.
10. The preparation method according to claim 8, characterized in that: The process parameters of the heat treatment in S3 are: heating temperature 165-300°C, holding time 2-4 h, followed by air cooling.